A reconstructive algorithm after thigh soft tissue sarcoma resection including predictors of free flap reconstruction✰. Issue 8 (August 2019) - Elswick, Sarah M.; Wu, Peter; Arkhavan, Arya A.; Molinar, Vanessa E.; Mohan, Anita T.; Sim, Frank H.; Martinez-Jorge, Jorys; Saint-Cyr, Michel
Summary: Background: Reconstruction of defects of the thigh after oncologic resection plays a vital role in limb salvage. Our goal was to evaluate our institution's experience on thigh sarcomas to develop evidence-based recommendations to guide the reconstructive surgeon, including factors that would predict the need for free flap reconstruction. Methods: We reviewed all thigh defects requiring plastic surgeon reconstruction following sarcoma resection at our institution from 1997 to 2014. Patient demographics, comorbidities, multimodality therapies, and operative characteristics were analyzed. Results: There were 159 thigh reconstructions. Reconstruction was achieved by primary closure (15%), skin graft (13%), local fasciocutaneous flap (8%), local muscle flap (31%), regional muscle flap (28%), or free flap (4%). For the proximal third of the thigh, the most common flaps were pedicled thigh muscle and rectus abdominis flaps; for the middle third of the thigh, it was pedicled thigh muscle flaps; and for the distal third, it was pedicled gastrocnemius muscle flaps. Factors shown to be predictive of requiring a free flap included wide defects ( p  = 0.03) and location in the middle third of the thigh ( p  = 0.001). Conclusion: There are multiple options for reconstructing defects from thigh STS. When primary closure and skin grafts are not an option, most defects can be closed with pedicled local or regional muscle or fasciocutaneous flaps. Free flap reconstruction is rarely required but can be necessary when defects are wide or located in the middle third of the thigh.